Education as a contradictory determinant of mental health between migrant and national adulthood. (30th September 2020) - Sesti, F; Minardi, V; Baglio, G; Bell, R; Goldblatt, P; Marceca, M; Masocco, M; Carrozzi, G; Fateh-Moghadam, P; Marmot, M
Abstract: The Social Determinants of Health (SDHs) are well known for their interaction on health outcomes and they can have a stronger impact on migrant health whom have higher probability to live in precarious living and working conditions compared to the hosting population. Migrant health is a public health issue which has to be considered taking into account the SDHs and complementary, including cultural issues is fundamental for addressing health equity in the society as a whole. Recognising this challenge, this study aims to evaluate the interactions between education and mental health of resident population in Italy, including Italians and immigrants. This study examined the respondents in 2014-17 to the Italian "Progressi delle Aziende Sanitarie per la Salute in Italia" (PASSI) surveillance system. The sample of 118, 639 respondents is composed by the residing working adults aged 25-69 with Italian citizenship (n = 112, 345) and foreign citizenship (n = 6, 294). Looking at SDHs, if for Italians high level of education appears to be a protective factor of mental health in accordance with the international evidence (adjPR: tertiary education 0, 87 95%IC 079-0, 97), among immigrants higher level of education it is more associated with the presence of depressive symptoms (adjPR: tertiary education: 1.77 95%IC: 1.19-2.63). Longer the length of stay in Italy for PFPM immigrants higher the risk of depressive symptoms: adjPR for 10+ years: 5.1 95%IC: 1.29-4.3. The data show that high education could represent a risk factor for mental health of immigrants. Considering that health is related to the nature of society as well as to access to technical solutions, multicultural societies require culturally oriented interventions for tackling health inequities. This means developing evidence-based policies in order to tackle health inequalities in the population as a whole, including culturally oriented measures in the larger framework of developing diversity sensitive services. Key messages: For some groups of population, such as migrants, high education could represent a risk factor for mental health. Developing diverse sensitive policies is needed in order to tackle health inequities in the population as a whole.